The commencement of knowledge. Rosmini critical heir of Hegel - Pagani, Paolo (Razón y fe, 2025)
This paper considers legacy of Hegel’s Wissenshaft der Logik in Rosmini’s Teosofia, on the starting point of knowledge. Hegel and Rosmini put back at the center of modern philosophical reflection the “Initial being”. This, which for both is the rightful starting point of knowledge, is an acquisition of late classical, and particularly scholastic, matrix. Both agree in recognizing in the being the character of self-manifestation, but the two authors diverge in the identification of the dialecticity that pertains to it. Hegel transfers to the being a dialectical motion proper to a knowing subject; Rosmini, on the other hand, seeks to identify tensions that belong to the being itself, considered in its abstractness.
Keywords: Hegel; Rosmini; Philosophy’s commencement; dialectics; initial being